Handbook of mechanical engineering calculations - Hicks, Tyler Gregory (McGraw-Hill, 1997)
The book offers solutions to thousands of problems in all areas of mechanical engineering, logical organization for accessibility - under the headings of power generation, plant and facilities engineering, environmental control, and design engineering, special coverage of software design validation, steam generation, environmental issues, gas turbine systems, and indoor energy conservation